(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Islamic boarding school-based entrepreneurship studies are studies that require students to become entrepreneurs or entrepreneurs. Entrepreneurial activity is one aspect of empowering the people’s economy. Al-Mawaddah Warrahmah Kolaka Islamic Boarding School is one of the Islamic boarding schools located in the middle of Kolaka, close to the center of the economy and the economic development sector. This position has opened up insight into entrepreneurship. In practice, Al-Mawaddah Warrahmah Kolaka Islamic Boarding School already has several business units, but the management does not involve students. Even though this is one step to create santripreneur. Therefore, there must be concrete steps taken by Islamic boarding schools to prepare santripreneurs to develop a sharia-based people’s economy, thus the most appropriate way to produce entrepreneurial spirited students is to provide entrepreneurship training assistance to students. The purpose of this service is expected to be able to create students at the Al-Mawaddah Warrahmah Kolaka Islamic boarding school to have business skills with a Sharia economic approach. The methods for implementing community service activities are the preparation stage, the service implementation stage, and the evaluation stage. The results of this activity, students have an understanding of sharia-based business, sharia financial management, sharia marketing management and are able to create products. The conclusion from the results of this community service activity is that creating sharia-based santripreneurs for Al-Mawaddah Warrahmah Kolaka Islamic boarding school students can be the main pillar of economic empowerment for the people in Kolaka Regency, Southeast Sulawesi.